Decomposition and nutrient content of leaf litter in a fragment of Atlantic Forest in the south of Espírito Santo - Silva, Aderbal Gomes da; Gonçalves, Marco Antonio Monteiro; Reis, Edvaldo Fialho dos (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
This study aimed to evaluate the decomposition of leaf litter and nutrient contents in the remaining mass, during the period of one year (2007). The study was conducted in the National Forest of Pacotuba, located in the municipality of Cachoeiro Itapemirim, ES. The decomposition rate was determined by installing 44 decomposition bags (Litterbags) in 11 permanent plots (40 m x 50 m), whose samples were collected quarterly during the year 2007. The decomposition rate (k) was 0.68, indicating an average of 575 days for a total renovation of the litter. The contents of N, P and Mg were homogeneous, without significant variations during the year, while the Ca and K showed significant variations, indicating heterogeneity in the levels of these elements during the decomposition of leaf litter.